(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
The new problematic sponge Sarsteinia babai n. gen., n. sp. is described from the Kimmeridgian to Tithonian Plassen and Lärchberg Formations of the Northern Calcareous Alps of Austria. The type-locality is the Sarsteinalm north of Mount Hoher Sarstein in the Austrian Salzkammergut, other findings come from Mount Sandling, Mount Jainzen, Mount Trisselwand and the Litzlkogel-Gerhardstein-complex west of Lofer. Most findings can be attributed to a fore-reef to upper slope facies or slope-of-toe breccias, small fragments can occasionally also be found in the back-reef facies. The suprageneric systematic position of the new sponge is unknown so far since it shows morphological characteristics known from Inozoa but also from "stromatoporoids".